EFEKTIVITAS PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) DALAM PEMBELAJARAN MAHASISWA UNIVERSITAS MUHAMMADIYAH BONE (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the effectiveness of Artificial Intelligence (AI) in the learning process of fourth-semester students in the Economics Education Study Program at Universitas Muhammadiyah Bone. The research is motivated by the rapid development of AI technology, which has the potential to improve learning quality, although its use among students remains uneven. This study aims to evaluate how effectively AI supports students in understanding materials, completing tasks, and accessing learning resources. A descriptive quantitative approach was applied using a Likert-scale questionnaire that has been tested for validity and reliability. The sample consisted of 65 active students who use AI platforms such as ChatGPT and Gemini. The results show an average effectiveness score of 4.0144, indicating that AI is effective in supporting learning. Therefore, students are encouraged to use AI wisely, and institutions are expected to provide digital literacy training to optimize its use.